PERANCANGAN SPECIAL MINI BOX STORAGE FOR CHILI FARMERS (SIBOCHIL) UNTUK MENINGKATKAN UMUR CABAI BERBASIS PENDINGINAN DAN PELEMBAPAN - Yahya Zefiansyah, Amin
In order to last long time and always be fresh, chili requires conditioned compartment for storage. This storage is expected to reduce the rate of chili damage both mechanically and physically. The air condition for chili storage is maintained in the temperature range 7-12oC and the relative humidity of 80-95%. The operation of the refrigeration system in the compartement results in dehumidification which a dramatic reduction in the weight of the chili. This weight loss can be seen from the profile of Equibrillium of Moisture Content (EMC) at constant temperature and humidity. In this final project, a refrigeration system has been design to produce a temperatureof 2oC and 95% relative humidity in the compartment for 50 kg chili weight, the cooling load is 968,9 Watts and the require condensate mass is 540 gram/hour. This design requires the following cooling and moisturizing system specifications: ? compressor : a cooling capacity of 985 Watts and 363 Watts of electrical power ? evaporator plate : aluminum material with an area of 0,72 m2 ? condenser fin and tube : 12 inches wide and 1,016 m/s fan speed ? capillary pipes : diameter = 2,16 mm with length = 5,39 m ? mist generator : 2 units with capacity of 800 ml/hour and 48 Watt of electricity load.